Phát triển hệ thống nhận diện màu sắc tự động cho bề mặt ván gỗ công nghiệp trong máy dán cạnh bằng công nghệ laser - Nguyen, Trong Tuan; Nguyen, Trong Tuan; Hua, Jun; Zhang, Bei Long; To, Quoc Huy; Tran, Cong Chi; Nguyen, Van Tuu; Nguyen, Tat Thang (TẠP CHÍ KHOA HỌC LÂM NGHIỆP, 2024)
Automatic color recognition is an important factor to achieve high levels of automation for laser edge banding system in furniture manufacturing. In this article, a color recognition system was designed and evaluated based on the Arduino UNO mainboard and TCS3200 sensor. The TCS3200 sensor was used to detect the color of the product, and the Arduino mainboard was used to read the output frequency and analyze the color result. Eight-panel surfaces with different colors were used to validate the accuracy of the designed system. The results showed that the design system had the ability to accurately identify colors with high stability. Therefore, this result might be applied for developing automatic color recognition systems in the next generations of laser-based edge sealing machine.